Comparison of Outcomes of Laparoscopic Cholecystectomy versus Robot Assisted Cholecystectomy - Effendi, Cemoon; Rasul, Shahid; Ali, Mansab; Wakil, Rafia; Aftab, Sana; Channa, Zoha Ainain (Indus Journal of Bioscience Research, 2025)
Objective: To compare outcomes of laparoscopic cholecystectomy versus robot assisted cholecystectomy in patients at tertiary care hospital, Karachi. Study Design: Randomized controlled trial. Duration and Place of Study: Department of General Surgery, Jinnah Postgraduate Medical Centre, Karachi from March 2025 to May 2025. Methodology: Total 96 patients (n=96) age 18–65 years were included and divided into two groups with 48 in laparoscopic group and 48 in robot assisted group. Data recorded for demographics and outcomes. Operative time, blood loss, bile spillage, wound complication and pain score were noted. Data analysed by independent sample t test and chi square test or Fischer exact test. Results: Mean age in laparoscopic group was 47.06 ± 9.87 years and in robot group 43.81 ± 9.98 years. Female were 26 (54.2%) in laparoscopic group and 30 (62.5%) in robot group. Operative time was more in robot group 81.81 ± 8.93 minutes as compared to laparoscopic group 57.13 ± 7.33 minutes (p<0.001). Blood loss was 40.88 ± 17.33 ml in laparoscopic and 43.10 ± 15.32 ml in robot group (p=0.506). Bile spillage seen in 7 (14.6%) laparoscopic and 11 (22.9%) robot group (p=0.296). Wound complication was 5 (10.4%) in laparoscopic and 2 (4.2%) in robot group (p=0.435). Pain score also not significant between groups (p>0.05). Conclusion: Both methods are safe and effective but robot assisted cholecystectomy take more operative time with similar outcomes.